Annealed Ti3C2Tx: A green and tunable electromagnetic interference shielding material. Issue 8 (15th April 2022) - Cheng, Xue; Liu, Ting-Ting; Wu, Da-Tong; Wu, Li-Li; Cao, Mao-Sheng; Gao, Hong
Abstract: Electromagnetic interference (EMI) shielding materials are receiving more and more attentions and becoming a hot research topic because of their wide range of applications in life, defense and other fields. The development of green EMI shielding materials with tunable shielding effectiveness (SE) is a high pursuit and a great challenge for researchers. Here, we restricted the growth of TiO2 on the Ti3 C2 Tx surface by adjusting the annealing temperature. This regulated the dipole and interface polarization and the construction of the conductive network, and improved the impedance matching. The Ti3 C2 Tx /TiO2 heterostructured material was rationally designed and achieved an efficient EMI SE of 35.1 dB at 18 GHz when the annealing temperature was 600 °C. This work develops new avenues for the future design of efficient, controllable green EMI shielding materials. Simultaneously, this heterostructured material has great potential as a versatile green shielding material for civil, commercial and military aerospace applications.